Sistem Informasi Manajemen Persediaan Obat Dengan Metode Fefo Dan Teknologi Barcode Pada Apotek Saras Mranggen - Yenita Aryana; Mustofa Andhy (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2022)
Merchandise inventory is the most important asset in the continuity of a trading business or shop. Toko Kudus Jaya is a retail trading business that sells hundreds of types of nuts and bolts of various types and sizes. The problem is that this store still uses manual recording in recording its merchandise inventory. This is considered vulnerable to various kinds of recording errors such as excess or shortage of inventory and is also considered less effective because it takes a lot of time in the recording process. The next problem is the procedure for ordering goods which only relies on sales estimates and is only carried out when the inventory has been exhausted without taking into account other costs at the time the order is placed. To solve these problems, the authors use Research And Development (R&D) as a product research and development method and the EOQ (Economic Order Quantity) method which is used to calculate the optimal number of orders by taking into account storage costs and ordering costs. The author designed a prototype web-based merchandise inventory management information system with the EOQ method, the PHP programming language, MySQL as the database and the bootstrap framework as the user interface. The application of web-based technology with the EOQ method is expected to help stores in their work activities so that they get data that is integrated in one database and can determine the number of orders so as to save costs incurred when placing an order.